2002
DOI: 10.1097/00004872-200209000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Adducin Gly460Trp polymorphism, left ventricular mass and plasma renin activity

Abstract: The homozygotic state of the allele of alpha-adducin polymorphism is independently associated with increased LV mass and low PRA. These data suggest that genetic considerations may contribute importantly to risk stratification, and perhaps therapeutic interventions targeted at LVH and the renin-angiotensin system in hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…The ␣-, ␤-, and ␥-subunits of adducin are encoded by genes (ADD1, ADD2, and ADD3 or Add1, Add2, and Add3 in humans and rats, respectively) that map to different chromosomes (29, 50). The polymorphism of ADD1 (G460W/S586C) alone (or in combination with those of ADD2) and angiotensin-converting enzyme is associated with either essential hypertension (18,45,78) or with the related cardiovascular and renal complications (51,54,60,70,75).The Milan hypertensive strain (MHS) of rats is a genetic model of hypertension in which cardiovascular phenotypes seem to be dependent, at least in part, on adducin gene polymorphisms (11,62). In the MNS ϫ MHS F2 hybrid population, the mutation of the Add1 gene accounts for the 50% of the blood pressure (BP) difference between MHS and its normotensive counterpart (MNS) (9, 11).…”
mentioning
confidence: 99%
“…The ␣-, ␤-, and ␥-subunits of adducin are encoded by genes (ADD1, ADD2, and ADD3 or Add1, Add2, and Add3 in humans and rats, respectively) that map to different chromosomes (29, 50). The polymorphism of ADD1 (G460W/S586C) alone (or in combination with those of ADD2) and angiotensin-converting enzyme is associated with either essential hypertension (18,45,78) or with the related cardiovascular and renal complications (51,54,60,70,75).The Milan hypertensive strain (MHS) of rats is a genetic model of hypertension in which cardiovascular phenotypes seem to be dependent, at least in part, on adducin gene polymorphisms (11,62). In the MNS ϫ MHS F2 hybrid population, the mutation of the Add1 gene accounts for the 50% of the blood pressure (BP) difference between MHS and its normotensive counterpart (MNS) (9, 11).…”
mentioning
confidence: 99%
“…However, a tendency towards a better antihypertensive response with achievement of target levels of SBP and DBP was revealed in patients with Trp-allele of the ADD1 Gly460Trp polymorphism, which is in agreement with other studies. In addition, many patients, carriers of the Trp/Trp-genotype, were classified as carriers of a "low-renin" form of HT (66.7 %) compared with other patients (23.8%) [29,30]. In contrast to the well-designed study on the ADD1 Gly460Trp polymorphism, some other studies in other populations have shown insufficient results to confirm the same correlation between ADD1 polymorphism and sodium sensitivity [29,31] or a response to diuretic therapy [32], which causes great interest in continuing the investigations.…”
Section: Discussionmentioning
confidence: 99%
“…52 Most studies on left ventricular hypertrophy have been performed in Caucasians. 48,49,[53][54][55][56][57][58] The majority did not find an association. 49,54 -58 In contrast, studies in Chinese dialysis patients, 59 South Korean patients with chest discomfort or hypertension 60 and Japanese outpatients of a cardiovascular clinic 61 found an association between TT genotype and cardiac hypertrophy.…”
Section: Angiotensinogen M235t Polymorphismmentioning
confidence: 99%